ENVIRONMENTAL LITERACY ON GARBAGE MANAGEMENT AND GREENING ‎ACTIVITY OF HIGH SCHOOL STUDENTS IN GREEN SCHOOL AND NON-GREEN ‎SCHOOL‎ - Ratri Wulandari; Eka Sulistiyowati (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
This survey research was conducted to understand the difference and level of environmental awareness and knowledge on solid waste management dan vegetation re-planting of students from Eco-School (adiwiyata) and Non Eco-School (non-adiwiyata). The number of respondents was 198 students from two high Eco-Schools (SMA N 1 Pengasih and MAN 2 Wates) and two high Non Eco-Schools (SMA N 1 Girimulyo and SMA N 1 Wates). Sample was chosen by random sampling. Students were given a set of questionnaires, which consisted section A tested students awareness and section B tested students knowledge. The data were statistically analysed using Mann-Whitney and descriptive statistics. The results of Mann-Whitney showed that there are significant difference on environmental awareness and knowledge between student taught in Eco-School and student taught in Non Eco-School (Sig.< 0,05). Meanwhile, the level of environmental awareness and knowledge between student taught in Eco-School and student taught in Non Eco-School are in the same level. The level of environmental awareness between student Eco-School and Non Eco-School is in the same low level and the level of environmental knowledge between student Eco-School and Non Eco-School is in the same low level. Keywords: Environmental literacy; Eco School (adiwiyata); solid waste management; vegetation re-planting